Baseline design of a sorption-based Joule-Thomson cooler chain for the METIS instrument in the E-ELT. (June 2017) - Wu, Y.; Zalewski, D.R.; Vermeer, C.H.; Holland, H.J.; Benthem, B.; ter Brake, H.J.M.
Highlights: The baseline design of a sorption JT cooler for METIS in E-ELT is presented. Three stages operate in parallel to provide cooling at 8 K, 25 K and 40 K. The design of the heat sink for optimum sink temperature are described. Experimental demonstrations plan of METIS cooler for further development is proposed. Abstract: METIS, the Mid-Infrared E-ELT Imager and Spectrograph, is one of the proposed instruments in E-ELT (European Extremely Large Telescope). Its infrared detectors require multiple operating temperatures below 77 K. Therefore, active coolers have to be deployed to provide sub-liquid-nitrogen (sub-LN2) temperature cooling. However, the sensitive imaging optical detecting system also demands very low levels of vibration. Thus, the University of Twente proposed a vibration-free cooling technique based on physical sorption. In this paper, we describe the baseline design of such a sorption-based Joule-Thomson cooler chain for the METIS instrument, that is able to deliver cooling powers of 0.4 W at 8 K, 1.1 W at 25 K and 1.4 W at 40 K from a 70-K heat sinking. This design is based on working fluid selection, cascading cooler stages and operating parameter optimization. Also, the performance of the resulting cooler design is analyzed.